Enhancing Students' Indonesian Language Skills through Interactive Learning at RA Imam Syafi'iy, Kota Bima - Darfiah; Eni Sastra (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to improve students' Indonesian language skills at RA Imam Syafi'iy, Kota Bima, through the implementation of interactive learning strategies. Indonesian language, as a fundamental subject in early education, plays a crucial role in enhancing students' communication and cognitive skills. Traditional teaching methods often focus on passive learning, which can hinder students’ active participation and engagement with the material. This research explores how interactive learning, which encourages student participation through discussions, role-playing, and practical exercises, can improve students' proficiency in Indonesian. The study was conducted in two cycles, involving kindergarten students at RA Imam Syafi'iy. Each cycle consisted of interactive activities such as storytelling, group discussions, and language games that allowed students to actively engage with the language. Data were collected through observations, student surveys, and pre- and post-assessments to evaluate changes in students’ language abilities, engagement, and motivation. The results of the research show that interactive learning significantly improved students’ Indonesian language skills. Students became more confident in using the language in both spoken and written forms. They also showed increased enthusiasm for learning, as the interactive activities made the lessons more engaging and fun. Furthermore, students demonstrated improved social and communication skills, as they actively participated in group discussions and language-based games. This study concludes that interactive learning is an effective approach to enhance young learners' language proficiency and foster a more engaging and collaborative classroom environment.